2020
DOI: 10.4300/jgme-d-20-00304.1
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study Comparing Effects of Call Schedules on Surgical Resident Sleep and Physical Activity Using the Fitbit

Abstract: Background Surgical residency training has an extended tradition of long hours. Residency programs use a variety of call schedules to combat resident fatigue and sleep deprivation while maintaining adherence to duty hour restrictions. Nonetheless, there is a paucity of data regarding objective measurements of sleep during the different call schedules included in general surgery training. Objective The primary objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…While prior studies have investigated the sleep duration of surgical residents, there is a notable gap in the literature regarding surgical fellows. A 2021 study of 26 general surgery residents reported an average of 4 h 44 min of sleep on home call nights, compared to 6 h 22 min on post-call nights [ 15 ]. Meanwhile, a 2017 study tracked ten urology residents and demonstrated an average of 2 h 45 min of sleep on home call nights, compared to 4 h on post-call nights [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies have investigated the sleep duration of surgical residents, there is a notable gap in the literature regarding surgical fellows. A 2021 study of 26 general surgery residents reported an average of 4 h 44 min of sleep on home call nights, compared to 6 h 22 min on post-call nights [ 15 ]. Meanwhile, a 2017 study tracked ten urology residents and demonstrated an average of 2 h 45 min of sleep on home call nights, compared to 4 h on post-call nights [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the studies investigating multiple dimensions of sleep health in physicians, few directly compare sleep log data to that from commercial wearable devices. Existing studies found in this area either rely on sleep logs alone, such as study of sleep banking in internal medicine residents by Cushman et al [ 32 ], or on Fitbit data alone, such as the study of 26 surgical residents wearing Fitbit devices on night float and home call [ 33 ]. To our knowledge, no study in physicians-in-training has directly compared sleep logs to commercial actigraphy device, which would allow for an evaluation of the external validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are affordable and user-centric commercial wearable devices that offer a modest amount of sleep data that can be transmitted through cloud systems, eliminating the requirement for proprietary software. For this reason, there is a growing volume of studies employing such commercial devices, for example, in research involving surgery residents [ 15 ], and internal medicine residents [ 16 ]. Nevertheless, in these investigations, there is still a lack of comparisons with manual sleep logs to ascertain the variance between self-report and sleep data derived from commercial wearable devices.…”
Section: Introductionmentioning
confidence: 99%
“…28,31,32 Surgical residents on rotations with in-house 24-h calls sleep significantly less than those on rotations with home call and night float. 33 Taken together, these findings suggest that residency training programs ought to prioritize the restructuring of rotations and teams to promote healthy sleep rhythms and allow time for exercise. Trainees should be granted time to attend to their own personal healthcare, including preventive care and chronic disease management, without fear of penalization or stigma.…”
mentioning
confidence: 94%